A novel technique for quantifying the fate of CO2 injected in oil reservoir for geological utilization and storage - Ting Hu; Yanfei Wang; Tianfu Xu; Hailong Tian; Zhenhua Rui; Yang Zhao; TingTing Liu (Energy Reports, 2023)
CO2-enhanced oil recovery (CO2-EOR) is a potential CO2 capture, utilization, and storage technology. In particular, CO2 can break the hydrochemical balance of water–rock and converts into carbonate minerals which are the most stable sequestration phase. The water–rock reactions are complex kinetic processes because the rate of dissolution/precipitation of minerals are vary with the pH of the formation water. However, studies on the effect of geochemical reactions on CO2-EOR processes are lacking, and the fate of CO2 cannot be accurately quantified. In this study, we combine the characteristics of the oil phase into the thermal–hydraulic–chemical TOUGHREACT simulator to consider various water–rock geochemical kinetic reactions in CO2-EOR. Therefore, the distribution phase of CO2 can be determined completely in the reservoir. Our analyses use the realistic fluid property (pressure–volume–temperature) of multicomponent oil phase–CO2 mixtures. The model considers the possible geochemical reactions and the resulting changes in porosity and permeability. The results indicate that in gas–water cycle of 9% hydrocarbon pore volume CO2 slug, the largest distributed phase of CO2 is the gas phase, accounting for 52.2% during the CO2 injection period. After water injection, the solubility of CO2 in the oil phase increases, and CO2 is mostly dissolved in the oil phase, accounting for 53.0%. Without considering the water–rock geochemical reactions will result in an underestimation of the dissolved aqueous phase and correspondingly the others were overestimated. The maximum error of the distributed quantity is up to 6.4% of the total injection. In addition, the omission of water–rock reactions result in an underestimation of the oil recovery. Comparing with the CO2 storage in a saline aquifer, dissolution of CO2 in oil phase in CO2-EOR scenario dampens the effect of buoyancy, which leads to higher sequestration capacity for the same footprint of storage reservoir.